Dietary Factors and Risk of Glioma in Adults: A Systematic Review and Dose-Response Meta-Analysis of Observational Studies - Zhang, Weichunbai; Jiang, Jing; Li, Xinyi; He, Yongqi; Chen, Feng; Li, Wenbin (Frontiers in Nutrition, 2022)
Background: Gliomas are the most common primary intracranial tumors in adults. Inappropriate dietary habits are thought to be a risk factor for many human cancers, and glioma is no exception. However, the effect of dietary factors on glioma is not clear. Objective: This review aims to quantitatively evaluate the association between various dietary intakes and glioma by meta-analysis. Methods: We searched articles on PubMed, Cochrane Library, Web of Science, and EMBASE from inception to 11 October 2021. According to heterogeneity, the fixed-effects model or random-effects model was selected to obtain relative risk of merger. Based on the methods described by Greenland and Longnecker, we explored the dose-response relationship between dietary intakes and the risk of glioma. Subgroup analysis, sensitivity analysis, and publication bias were also used for analysis. Results: The study reviewed 33 articles, including 3606015 controls and 8831 glioma patients. The study included 12 food groups. Compared with the lowest intakes, the highest intakes of tea (relative risk (RR)=0.82, 95% confidence interval (95%CI):0.71-0.93), total vegetables (RR=0.84,95%CI:0.70-1.00), green vegetables (RR=0.80, 95%CI:0.66-0.98), and orange vegetables (RR=0.79,95%CI:0.66-0.96) significantly reduced the risk of glioma, while the highest intakes of grains (RR=1.39,95%CI:1.16-1.66), processed meats (RR=1.19,95%CI:1.00-1.42), and processed fish (RR=1.37,95%CI:1.03-1.84) significantly increased the risk of glioma. The results of subgroup and sensitivity analysis remained unchanged. In the dose-response relationship, only tea was statistically significant. Taking an extra cup of tea every day reduced the risk of glioma by 4%. Conclusions: Our analysis suggests that the intakes of tea, total vegetables, green vegetables, and orange vegetables may reduce the risk of glioma, while the intakes of grains, processed meats, and processed fish may increase the risk of glioma. Therefore, the effect of dietary factors on glioma should not be ignored.